Penatalaksanaan Holistik Pasien Lansia dengan Hipertensi Derajat 1, Diabetes Mellitus Tipe 2, Obese Grade I, dan Hiperkolesterolemia Melalui Pendekatan Kedokteran Keluarga di Puskesmas Rawat Inap Kedaton - Dinda Afifa; Tutik Ernawati; Adela Putri Agata (CV. Jasa Sukses Abadi, 2022)
Hypertension is one of the degenerative disease. Degenerative disease is a chronic non-communicable disease due to deterioration in organ function due to the aging process. The prevalence of hypertension in lampung reached 7,95%. Through identifying the risk factors, clinical problems, conduct patient management holistically by applying family doctors according to evidence based medicine through a patient center, family approach, and community oriented. This study is a case report. The primary data obtained through anamnesis, physical examination, and home visits to complete the family data, psychosocial and environmental data. Assessment based upon a holistic diagnosis of early, process, and the final quantitative and qualitative studies. Based on a holistic diagnosis, the patient had a history of hypertension and type 2 diabetes mellitus for more than 10 years, as well as hypercholesterolemia and obesity. Patients routinely seek treatment at the clinic and routinely take medication every day. The patient's diet is still irregular and the patient rarely does physical activity. The diagnosis and managemet of the patient has been done holistically, patient centered, family approach and in accordance with national guidelines and based on evidence based medicine. Changes in patient and family knowledge and behaviour occur after patient center and family approach interventions.